BLOOD FLOW SIMULATION METHOD AND APPARATUS FOR SUBJECT-SPECIFIC BLOOD VESSEL (2020)
In a simulation method according to the present invention, when performing a blood flow simulation by coupling a CFD model and an LPM model, a blood flow simulation for the CFD model is performed under a set initial condition and a boundary condition, a blood flow rate Qi for each outlet and a total outflow blood flow Qtot_cfd of the CFD model are calculated by a blood flow simulation, the microvascular bed parameters of the LPM model are updated using the blood flow rate for each outlet and the total outflow blood flow of the CFD model, the boundary condition of an outlet of the CFD model is updated using the updated LPM model, and the simulation is repeatedly performed until a convergence condition of the blood flow simulation for the CFD model is satisfied, thereby calculating blood flow information for the three-dimensional blood vessel model.